Pengantar Metodologi Studi Islam - Bintan Kamila; Siti Dhafa Shofiatul Atcqia; Muhamad Arwansyah; Maftuh Ajmain (PT. Saha Kreasi Indonesia, 2026)
This study aims to explain the meaning of Islamic studies methodology, identify the main and supporting sources in Islamic studies, analyze the scope of Islamic studies, describe various approaches in Islamic research, and understand the importance of Islamic studies methodology in the modern era. The method used is library research with a descriptive-analytical approach to literature related to Islamic studies methodology. The results show that Islamic studies methodology is a scientific framework used to examine Islamic teachings, history, thought, and practice systematically and directionally. The sources of Islamic studies include the Qur'an, hadith, ijtihad and reason, as well as social reality and scholarly traditions. The scope of Islamic studies includes creed (aqidah), sharia, ethics and sufism, history and civilization, as well as Islamic thought and contemporary issues. Approaches in Islamic research include normative-theological, historical, sociological, anthropological, philosophical, and interdisciplinary approaches. Islamic studies methodology is very important in the modern era to produce a moderate, contextual, and scientific religious understanding.